Study on Stability Control of Retained Gob-Side Entry by Blasting Fracturing Roof Technology in Thick Immediate Roof - Jingang Guo; Yaohui Li; Fulian He; GuangSheng Fu; Sheng Gao (Shock and Vibration)
A retained gob-side entry technique is popular in longwall mining coal mines, because the excavation of an entry is reduced for the next panel. However, it is influenced by multiple excavations and mining, so the stability control of the surrounding rock becomes a problem. In view of the above problems, a typical retained gob-side entry with thick immediate roof was carried out, and a blasting fracturing roof technology was used in it to improve the stress environment, reduce the deformation and damage, and ensure stability and safety. To study the fracturing roof parameters, a global model with thick immediate roof considering strain-soft and double-yield constitution was built. It found that the stress, damage range, and deformation of surrounding rock were closely related to the height and angle of fracturing roof, and an optimal case was given out. The simulation result was applied to the field practice, and a good application effect was achieved. The above technique and research method can be used as a reference for the coal mine with similar conditions.